2017
DOI: 10.4172/2329-8731.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Rheumatoid Arthritis in an Inner City Population with Sickle Cell Disease

Abstract: Objectives Rheumatoid arthritis (RA) has been rarely reported in association with sickle cell disease (SCD). Our study aimed to estimate the prevalence of RA in SCD population and to describe the clinical characteristics of RA associated with SCD. Methods Retrospective chart review of SCD and RA patients followed at 2 large urban hospitals. Seven RA/SCD patients were identified and compared to age and sex matched cohort of SCD only and of RA only group. All patients were Black. Results There were 739 SCD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Michel et al performed a retrospective study analyzing connective tissue disease in patients with SCD. There were 15 patients identified with RA coexisting with SCD, with 93% having rheumatoid factor positivity, 88% having anti-citrullinated peptide antibodies and 80% had erosive joint disease [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Michel et al performed a retrospective study analyzing connective tissue disease in patients with SCD. There were 15 patients identified with RA coexisting with SCD, with 93% having rheumatoid factor positivity, 88% having anti-citrullinated peptide antibodies and 80% had erosive joint disease [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SCD-RA patients were also older than the SCD-only population but younger than RA-only patient population and had been diagnosed with RA at a younger age (about 5 years earlier) than RA-only patients. SCD-RA patients had more difficulty with ADL [ 25 ]. We hypothesize that improved survival of SCD patients resulting from medical care, preventive measures such vaccinations and the introduction of hydroxyurea, have made SCD population susceptible to the development of RA that generally occurs at a more advanced age [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal manifestations of sickle cell disease (SCD) may delay the diagnosis of inflammatory forms of arthritis, but in the case of persistent joint involvement, RA should be considered as a diagnosis, given the early and irreversible dysfunction related to the disease. Besides the case reports in literature (Table I), two important retrospective studies have demonstrated that a longer life expectancy for SCD patients correlates with a greater increase in the prevalence of RA (Michel et al 1 , 2 . We describe the coexistence of RA with SCD in six Afro‐descendant women (Table II) to emphasise the importance of early diagnosis and specific treatment, given that bone erosions become evident within less than three months of disease duration, particularly in untreated patients.…”
Section: Reference N Age and (Scd Form) Treatment Outcomementioning
confidence: 99%
“…The management of RA in SCD patients is a dilemma because of the potential risks and benefits of interventions in terms of infection and immunosuppression. The permanent inflammatory state, as a consequence of the vaso‐occlusive crisis and haemolysis, might be a factor in the severity of the first years of RA 2 …”
Section: Reference N Age and (Scd Form) Treatment Outcomementioning
confidence: 99%